Comparison of Luminescence in LiGaO2, Al2 O3 -Ga and Al2 O3 -Li Crystals - Trukhin, Anatoli; Trinkler, Laima; Chou, M.M.C. (Sciendo, 2018)
We have studied luminescence of LiGaO 2 , Al 2 O 3 -Ga and Al 2 O 3 -Li crystals in order to reveal the nature of luminescence centres and mechanisms in these crystals. In Al 2 O 3 -Ga presence of Ga impurities determines occurrence of the 280 nm emission band, which demonstrates intra-centre character in photoluminescence and recombination character under X-ray irradiation. In Al 2 O 3 -Li crystal lithium induced luminescence is presented with the 326 nm band, which has a recombination character. Basing on spectral similarity of the main luminescence bands in pure LiGaO 2 crystal with the dopant-induced emission bands in Al 2 O 3 , and on peculiarities of the X-ray induced thermoluminescence, the adjustment of the previous luminescence interpretation is done. It is proposed that the donor-acceptor pairs with random separation distribution responsible for the 280 nm emission are represented with gallium Ga (plus an electron) and O (plus a hole) pairs, while the donor-acceptor pairs, producing the 330 nm emission band contain a lithium ion, presumably in the interstitial position Li i , and a neighbouring oxygen ion with a caught hole.
Keywords: alumina; donor-acceptor pairs; exciton; lithium metagallate; luminescence; Research Subject Categories::NATURAL SCIENCES:Physics